PENGEMBANGAN E-LKPD BERBASIS SALINGTEMAS (SAINS, LINGKUNGAN, TEKNOLOGI, MASYARAKAT) MATERI PERUBAHAN LINGKUNGAN KELAS X SMA - Aslam, Muhammad; Azis, Andi Asmawati; Adnan, Adnan (Jurnal Biotek, 2021)
This R & D research aimed to know the category of validity, practicality, effectiveness, and specifications of e-LKPD based on Salingtemas. The product developed with the ADDIE development model consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted at SMAN 1 Tinambung with 30 students from class X MIA 2 and 12 biology teachers. The validation sheets of e-LKPD, teacher response questionnaires, student response questionnaires, implementation observation sheets, and multiple-choice tests were used as instruments. Data on the level of validity and practicality were collected using a questionnaire, while the data on the level of effectiveness was collected through a learning outcome test. Based on the results of the data analysis of the validity of the e-LKPD based on Salingtemas, it obtained an average value of 4.7 with a valid category. The total average score percentage for the teacher’s response questionnaire was 92 with a positive response category, while the total average score percentage for student responses was 87 with a positive response category. The observations showed an average percentage value of 95.4 as well-implemented. The students’ test results were 93 percent effective in this category. It appears that the developed Salingtemas-based e-LKPD has met the valid, practical, and effective categories.